PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN ALAT PERAGA UNTUK MENINGKATKAN HASIL BELAJAR MATERI PEMBAGIAN - Sasi, Putri Kusnawang; Nuro, Falistya Roisatul Maratin; Sahara, Indah Fida (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This study aims to describe the increase in student learning outcomes in dividing learning using teaching aids in class IV SDN Lowokwaru 2 Malang City. This study used the Problem Based Learning (PBL) learning model in the form of classroom action research and was carried out in two cycles. Data collection techniques were direct observation techniques and measurement techniques. Data collection tools used observation sheets and tests. The results of research on the teacher's ability to compose teaching modules on average cycle 1 reached 3.14 increased in cycle II reached 3.71, the ability of teachers to carry out learning in cycle 1 received an average of 2.92 increased in cycle II reached an average of 3, 75 while student learning outcomes in cycle I averaged 67.67 with the completeness of 15 people increased in cycle II with an average value of 87.50 with 27 students' completeness. The data above shows the teacher's ability to compile and carry out learning and student learning outcomes in learning mathematics about the distribution of using visual aids in class IV students has increased.